Explicação passo-a-passo:
a) 149+23 -1= 172 - 1= 171
b) 5 - { 3 - [ 4 - (+25) +6 -4]}=
5 - { 3 - [ 4-25 +6-4]}=
5 - { 3 - [ - 19]}=
5 - { 3 +19}=
5 - { 22}=
5 -22=
-17
b) 15 - { -3 + [ (5 - 62 .(9-8)²+1]}=
15 - { -3 + [ (5 - 62 . 1² +1]}=
15 - { -3 + [ 5 -62 .1+1]}=
15 - { -3 + [ 5-62 +1]}=
15 - { -3 + [ -56]}=
15 - { -3 - 55}=
15 - { - 58}=
15 +58=
73
c) 18 - { 6 - [ -3 - (+1) - (-2)] -1}=
18 - { 6 - [ -3-1+2] -1}=
18 - { 6 - [ -4+2] -1}=
18 - { 6 - [ -2] -1}=
18 - { 6 +2-1}=
18 - { 8-1}=
18 - { 7}=
18 -7=
11